Application of Macro and Micro Fertilizers on Upland Rice Crops Inoculation of Biofertilizers in Bengkulu Coastal Land - A. Lestari; Riwandi Amir; Yudhy Harini Bertham (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
Coastal land located in the lowlands near the coast has a marginal Entisol soil type. Entisols have the following characteristics: loose soil aggregate, sensitive to erosion, and low levels of nutrients, organic matter, water holding capacity, and soil fertility. The nature of this Entisol is less able to produce maximum upland rice production. The technology used to overcome this problem is by applying macro and micro fertilizers to the soil, which is planted with upland rice seeds, inoculated with biological fertilizers so that it is hoped that upland rice production can be maximized. The purpose of this study was to obtain high upland rice production in coastal areas. The research was carried out from June to December 2020 in Beringin Raya Village, Muara Bangkahulu District, Bengkulu City. The research location is located at coordinates S 03?45'23'' E 102?15'41''. The experimental design used was Completely Randomized Block Design (CRBD) with 2 factors, namely types of fertilizers and varieties of upland rice. The first factor consists of P0 = No fertilizer; P1 = compound micro fertilizer; P2 = Fertilizer recommended for upland rice from the Institute for Agricultural Research and Technology). The second factor consists of V1 = red upland rice; V2 = white upland rice) The results showed that there was an interaction between the type of fertilizer and upland rice varieties on soil pH (KCl 1:2.5 w/v). the interaction of microfertilizers with white upland rice varieties resulted in the highest soil pH (5.06). The best type of fertilizer is micro-compound fertilizer which produces soil pH (KCl 1:2.5 w/v), P nutrient uptake, the highest root colonization and the highest number of production tillers and the highest grain weight per plant and upland rice yield per plot. The best upland rice variety was the white variety which produced the highest uptake of P nutrients, the number of productive tillers, the weight of grain per plant and the highest yield per plot.